Derivative margin calls: A new driver of MMF flows - Maddalena Ghio; Linda Rousová; Dilyara Salakhova; Germán Villegas Bauer (European Central Bank (ECB), 2023)
During the March 2020 market turmoil, euro area money-market funds (MMFs) experienced significant outflows, reaching almost 8% of assets under management. This paper investigates whether the volatility in MMF flows was driven by investors' liquidity needs related to derivative margin payments. We combine three highly granular unique data sources (EMIR data for derivatives, SHSS data for investor holdings of MMFs and Refinitiv Lipper data for daily MMF flows) to construct a daily fund-level panel dataset spanning from February to April 2020. We estimate the effects of variation margin paid and received by the largest holders of EUR-denominated MMFs on flows of these MMFs. The main findings suggest that variation margin payments faced by some investors holding MMFs were an important driver of the flows of EUR-denominated MMFs domiciled in euro area.
Keywords: G13; G15; G23; 330; liquidity risk; money market funds; big data; interconnectedness; non-bank financial intermediaries